Antiplatelet therapy in patients with coronary artery stents for noncardiac surgery: Role of thromboelastography - Rashmi Jain; Jayashree Sood (Journal of Anaesthesiology Clinical Pharmacology, 2011)
The perioperative course of the patients who have undergone coronary stent placement was studied. These patients were on dual antiplatelet therapy and were posted for noncardiac surgery. Clopidogrel had been discontinued for a variable duration before noncardiac surgery. Thromboelastography (TEG) was performed preoperatively to assess their fitness for surgery. The surgery and the postoperative period were uneventful in all the patients. There was no incidence of increased bleeding in any of the patients. Blood transfusion was not required in any patient. We concluded that standard TEG can be used when in dilemma about the fitness of the patient for surgery. Although there are clear guidelines about the patients who are on dual antiplatelet therapy, in clinical practice, it is important to weigh the risk-benefit to the advantage of the patient. If we stop the dual antiplatelet therapy in a patient with drug eluting stent within 1 year of implantation, the risk of major adverse cardiac event increases many fold. If we continue clopidogrel and aspirin during surgery, the risk of bleeding increases but is not life-threatening, except when surgery is performed in closed spaces. Thus, to continue dual antiplatelet medication intraoperatively is better than to stop it. If the medicine has to be withheld, it should be withheld for the minimal possible duration and a TEG should be performed.